Towards efficient photoinduced charge separation in carbon nanodots and TiO2 composites in the visible region. Issue 12 (27th February 2015) - Sun, Mingye; Qu, Songnan; Ji, Wenyu; Jing, Pengtao; Li, Di; Qin, Li; Cao, Junsheng; Zhang, Hong; Zhao, Jialong; Shen, Dezhen
Abstract : The visible photoinduced electrons and holes in CDs-V/TiO2 composites could be effectively separated, indicating that a well performing CD-based photovoltaic system could be realized. Abstract : In this work, photoinduced charge separation behaviors in non-long-chain-molecule-functionalized carbon nanodots (CDs) with visible intrinsic absorption (CDs-V) and TiO2 composites were investigated. Efficient photoinduced electron injection from CDs-V to TiO2 with a rate of 8.8 × 10 8 s −1 and efficiency of 91% was achieved in the CDs-V/TiO2 composites. The CDs-V/TiO2 composites exhibited excellent photocatalytic activity under visible light irradiation, superior to pure TiO2 and the CDs with the main absorption band in the ultraviolet region and TiO2 composites, which indicated that visible photoinduced electrons and holes in such CDs-V/TiO2 composites could be effectively separated. The incident photon-to-current conversion efficiency (IPCE) results for the CD-sensitized TiO2 solar cells also agreed with efficient photoinduced charge separation between CDs-V and the TiO2 electrode in the visible range. These results demonstrate that non-long-chain-molecule-functionlized CDs with a visible intrinsic absorption band could be appropriate candidates for photosensitizers and offer a new possibility for the development of a well performing CD-based photovoltaic system.